2020
DOI: 10.3389/fpsyt.2020.503274
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology, Body Image and Quality of Life in Female Children and Adolescents With Anorexia Nervosa: A Pilot Study on the Acceptability of a Pilates Program

Abstract: Background: Anorexia nervosa (AN) is a psychiatric illness that without early effective treatment becomes chronic with high physical, psychological and social morbidity and high mortality. Pilates exercises can improve quality of life and increase body awareness in different clinical and healthy populations. The aim of this pilot study was to examine the acceptability of a Pilates program in a sample of female children and adolescents with AN by evaluating the psychopathological status, alterations in the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Thøgersen-Ntoumani et al 52 58 on women treated for breast cancer, it was determined that pilates exercise method gave more positive results than belly dance. Martínez-García et al 59 found that pilates exercises applied 3 times a week for 10 consecutive weeks in girls and adolescents with anorexia nervosa decreased body image dissatisfaction and increased physical satisfaction. There are also findings in the literature that are not parallel to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Thøgersen-Ntoumani et al 52 58 on women treated for breast cancer, it was determined that pilates exercise method gave more positive results than belly dance. Martínez-García et al 59 found that pilates exercises applied 3 times a week for 10 consecutive weeks in girls and adolescents with anorexia nervosa decreased body image dissatisfaction and increased physical satisfaction. There are also findings in the literature that are not parallel to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 28 selected reports, we found seven reports corresponding to three studies (i.e., same sample, same trial number, same authors, same hospital): the two reports of Szabo & Green ( 49 ) and Chantler et al ( 50 ) were from the same study; the three reports of Fernandez-del-Valle et al ( 51 ), Fernandez-del-Valle et al ( 52 ) and Fernandez-del-Valle et al ( 53 ) were from the same study; and the two reports of Martinez-Sanchez et al ( 54 ) & Martinez-Sanchez et al ( 55 ) were from the same study.…”
Section: Resultsmentioning
confidence: 94%
“…The 28 reports from the 27 studies included and examined in this review aimed to assess the effects of ET on ED symptoms and/or on the physical and/or mental health of patients with AN. Thirteen studies were RCTs ( 49 53 , 56 – 63 ), 8 studies were NRCTs ( 8 , 64 70 ), and 6 studies were UTs ( 54 , 55 , 71 75 ). All studies included patients with a diagnosis of AN; 11 studies also included patients with other ED as well ( 58 60 , 62 , 63 , 66 , 69 , 70 , 72 74 ); while 16 of the 27 studies included only patients with AN ( 8 , 49 57 , 61 , 64 , 65 , 67 , 68 , 71 , 75 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, all the studies mentioned previously agree that female adolescents are the more vulnerable group. It is for this reason that all interventions that include the aforementioned parameters in clinical samples (anorexia nervosa) have obtained satisfactory results by contributing to the improvement of self-perception (as it helps reduce body dissatisfaction), thus having a direct impact on the reasons for dieting [40] above mentioned.…”
Section: Introductionmentioning
confidence: 99%